Математична модель розрахунку складній траєкторії маніпулятора на основі систем рівнянь Лагранжа 2-го роду - Бурченко, Александр Дмитриевич; Солодовник, Михаил Дмитриевич (Eastern-European Journal of Enterprise Technologies, 2010)
A mathematical model for calculating the complex elliptic manipulator trajectory based on the systems of equations of Lagrange is developed